Contracting on litigation. - Spier, Kathryn E.; Prescott, J.J. (RAND Journal of Economics (Wiley-Blackwell))
Two risk‐averse litigants with different subjective beliefs negotiate in the shadow of a pending trial. Through contingent contracts, the litigants can mitigate risk and/or speculate on the trial outcome. Contingent contracting decreases the settlement rate and increases the volume and costs of litigation. These contingent contracts mimic the services provided by third‐party investors, including litigation funders and insurance companies. The litigants (weakly) prefer to contract with risk‐neutral third parties when the capital market is transaction‐cost free. However, contracting with third parties further decreases the settlement rate, increases the costs of litigation, and may increase the aggregate cost of risk bearing.